2009
DOI: 10.1007/s11240-009-9527-9
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of isolated microspore culture of pepper (Capsicum annuum L.) via co-culture with ovary tissues of pepper or wheat

Abstract: The influence of the developmental stage of microspores on establishing isolated microspore cultures of three Hungarian ('Szegedi 80', 'Szegedi 178', and 'Remény') and three Spanish ('Jeromin', 'Jariza', and 'Jaranda') pepper genotypes was investigated. Donor anthers containing 80% uninucleated and 20% binucleated microspores yielded the highest frequency of successful microspore cultures. Cocultures with wheat, line 'CY-45', ovaries exhibited enhanced frequency of embryoid production than those with pepper ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 34 publications
4
39
0
2
Order By: Relevance
“…These results, i.e. genotype dependence on androgenic response are in consistent with the reports of several earlier workers (Dumas de Vaulx et al, 1981;Rodeva et al, 2004;Lantos et al, 2009;Zhao et al, 2010;Niklas et al, 2012;Liljana et al, 2013;Luitel andKang, 2013 andOlszewska et al, 2014).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These results, i.e. genotype dependence on androgenic response are in consistent with the reports of several earlier workers (Dumas de Vaulx et al, 1981;Rodeva et al, 2004;Lantos et al, 2009;Zhao et al, 2010;Niklas et al, 2012;Liljana et al, 2013;Luitel andKang, 2013 andOlszewska et al, 2014).…”
Section: Resultssupporting
confidence: 92%
“…equivalent to a bud size having sepals and petals of equal length. Similar bud size was reported to be best for callus induction and regeneration by Lantos et al, (2009).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The most frequently measured whorls have been corolla (Dunwell 2010) and calyx, where the ratio between calyx and corolla has been the most used parameter (Koleva-Gudeva et al 2007;Ltifi and Wenzel 1994;Mityko et al 1995;Nowaczyk and Kisiala 2006). Other authors opted for a direct estimation of the degree of purple antocyanin pigments that anthers of many pepper types accumulate during their development (Regnet 1994;Kim et al 2008;Kim et al 2004) or by a combination of this marker with the calyx/corolla ratio (Barany et al 2005;Barany et al 2010;Buyukalaca et al 2004;Dumas de Vaulx et al 1981;Supena et al 2006b;Supena et al 2006a;Ercan et al 2006;Lantos et al 2009). From these reports it can be concluded that there is no a wide consensus with respect to the most suitable marker to define which pepper flower buds should be used to maximize the percentage of VM and YBP.…”
Section: Introductionmentioning
confidence: 99%
“…However a cold temperature stress is not a requirement for other species such as asparagus (Wolyn and Nichols, 2003), pepper (Lantos et al 2009), or Saponaria vaccaria L. (Kernan and Ferrie 2006).…”
Section: Growing Donor Plantsmentioning
confidence: 99%